EMPOWERMENT AND IMPROVEMENT OF FAMILY WELFARE GOVERNMENT PROGRAM FOR COUPLES WITH DISABILITIES AURA LENTERA BANYUWANGI - Putri Robiatul Adawiyah; Hadi Jatmiko (POLITICO, 2022)
This research aims to overcome the problem of Empowerment and Inmprovement of  Family Welfare for Couples with Disabilities Aura Lentera Banyuwangi. The purpose of this research is to overcome the problems of Partner Problems, namely there is still no continuity of empowerment programs carried out by the government for family couples with disabilities. Generally, training is only for persons who are still in their teens or in school. Some Based on these data, other problems can be identified as follows: 1. Many women and wives with disabilities become the main support for the family and help their husbands who have disabilities; 2. There are several couples, in general there are dominant partners who both have limitations as persons with disabilities, both husband and wife; 3. There is still a lack of Family Economic empowerment programs for people with visual impairments and other disabilities for people who are already married; 4. Lack of Accessibility Welfare Program for families with visual impairments and people with other visual impairments is still rare; 5. Pro-disability government policy programs. However, this information has not yet arrived or has not been reached by persons with disabilities; 6. Problems with limitations in improving the economy and family welfare of spouses with disabilities; 7. Government programs that have been made for all components of society are not yet accessible, especially for vulnerable groups, especially people with disabilities, both visually impaired and other handicapped; 8. Accessibility of information on economic empowerment and education is still not easily accessible to persons with disabilities, especially the visually impaired; 9. There is no family economic empowerment starting from family spiritual development; 10. Education is still rare in maintaining environmental cleanliness and health with healthy and halal eating patterns; 11. There has been no special socialization for groups of people with families who are already married to exercise regularly to be healthy and avoid various kinds of diseases; 12. Training is still rare in accordance with the limitations and competencies possessed by persons with disabilities, both visually impaired and other handicapped. Just a little like massage training. Forms of business skills to increase household income, such as home industry business skills to date are making cakes, and salted eggs. As well as some visually impaired persons who have vocal abilities and are members of the Al Mumtaz MSME arts community, which have not been accommodated in a sustainable manner. The solutions offered are 1. By holding a socialization of government programs for the disabled, inviting BLK and Welfare of the Banyuwangi Regency Government to share discussions; 2. Family economic empowerment, family spiritual development, self-actualization motivation in the fields of education, health, economy; 3. Socialization of healthy living, healthy and halal eating patterns; 4. Community motivation; 5. Accessibility of information on empowerment programs The output targets to be achieved are increased understanding of training participants, increased accessibility of Banyuwangi district government programs and hopes for improving the welfare of families with persons with disabilities; publication of online media and print media, compiling articles related to service in the form of national journals, photos and videos of activity documentation.Keywords: Empowerment; Accessibility; Women's Welfare; Government Program; Aura Lantern